The Effectiveness And Safety Of Oral Microbial Agents As An Adjunct Therapy For Atopic Dermatitis: A Systematic Review - Sylvia; Daniel (International Medical Journal Corp. Ltd, 2024)
Background: Eczema, also known as atopic dermatitis (AD), is a chronic inflammatory skin condition that significantly impacts the quality of life for both children and adults, affecting up to 20% of children and 10% of adults globally. While topical corticosteroids (TCS) have been the primary treatment, their long-term use can lead to adverse side effects and corticophobia, underscoring the need for alternative therapies like microbial agents (MA) which have shown promise in improving eczema symptoms and reducing reliance on TCS. Methods: This systematic review focused on full-text English literature published between 2014 and 2024 using the PRISMA 2020 guidelines. The literature was compiled using PubMed, ScienceDirect, and SagePub, among other online venues. Result: Five publications were found to be directly related to our ongoing systematic examination after a rigorous three-level screening approach. Conclusion: This systematic review suggests that microbial agents (MA) are a promising add-on therapy for moderate to severe eczema in children when used alongside topical corticosteroids (TCS). Mixed-strain probiotics and synbiotics showed the most significant improvement in eczema severity, but the optimal dosage and steroid-sparing effect require further investigation. Future research should explore MA's effectiveness across different age groups and severities of eczema.